2010
DOI: 10.1590/s0004-282x2010000500016
|View full text |Cite
|
Sign up to set email alerts
|

Is West Nile virus a potential cause of central nervous system infection in Brazil?

Abstract: Meningitis and encephalitis are complications of West Nile virus (WNV) infection. Although WNV is endemic in North America, the virus has recently been reported in Colombia and Argentina. Investigation of WNV in Brazil is important since this virus has never been studied previously in this country. Objective: To investigate the presence of WNV infection in viral encephalitis/meningitis cases of unknown etiology in the city of Rio de Janeiro, Brazil. Method: Thirty-seven adults with viral meningitis/encephaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…WNV seropositivity was also reported in an equine sample collected in 2009 in Paraiba state in northeastern Brazil [ 313 ]. However, WNV has not yet been associated with human or equine illness in Brazil [ 314 ].…”
Section: Wnv In South Americamentioning
confidence: 99%
“…WNV seropositivity was also reported in an equine sample collected in 2009 in Paraiba state in northeastern Brazil [ 313 ]. However, WNV has not yet been associated with human or equine illness in Brazil [ 314 ].…”
Section: Wnv In South Americamentioning
confidence: 99%
“…E-mail: macsvieira@superig.com.br several other viral infections of the central nervous system, and 3) the limitations in the availability of diagnostic resources in most Brazilian hospitals. 2,4,[11][12][13] Since the detection of this first human case of WNV encephalitis in Brazil, strategies for a prospective approach to new cases are being implemented. Preliminary serologic studies performed among chickens and equines on the patient's farm showed the presence of specific antibodies against WNV confirmed by PRNT 90 .…”
Section: Case Presentationmentioning
confidence: 99%
“…The last report from South America came from Brazil, where neutralizing antibodies against the virus were found in horses in 2009 and in birds in 2010,[3536] nevertheless no human cases were found after a screening of patients that year. [37] For some reason, there are no reports in several countries from Central and South America and also for some Caribbean Islands; although, all have the variables that could favor the circulation of the virus. There are also reports of WNV circulation in neighboring countries.…”
Section: Introductionmentioning
confidence: 99%